Incorporação do resíduo oriundo do beneficiamento de caulim em concreto asfáltico - Costa, Cibele Gouveia (2006)
The municipal district of Equador-RN is located in an area of great amounts of ores, being your main economical activity the extraction and the kaolin improvement. The main originating from environmental problem that activity is the amount of generated residue, about 70% of the extracted kaolin. The residues are simply piled up in lands of the improvement companies, occupying like this a large area and causing impact in the existent flora. When dry, the residues transform powdered and for the action of the wind, they disperse, polluting the air. Being like this, the present work has as objective evaluates the incorporation of the great residue, originating from of the kaolin improvement, in partial substitution of all the employed aggregates in a conventional mixture of asphalt concrete, which was used in the paving of BR101/RN061 - passage between Ponta Negra and Ares. That evaluation was accomplished in three stages. The first refers to the evaluation of the physical, thermal and mineralogical characteristics of the residue with the intention of to classify it and to define your application as aggregate (small and great). The second refers to the physical characterization of the aggregates and of the asphalt material used in the conventional mixture. And the third, to the evaluation of the mixtures containing residue, which were elaborated starting from the conventional mixture with the gradual incorporation of the residue, from 5 to 40%, in substitution to the part of the conventional aggregates, in way to obtain similar particle size curves the one of the conventional mixture. That evaluation was accomplished through the comparison between the volumetric composition, the mechanical behavior and the susceptibility to the humidity of the mixtures containing residue with the one of the conventional mixture, and with the one of the DNIT specifications. The results show that the great residue originating from of the kaolin improvement has grains of the most varied size, being like this, it can substitute part of all the conventional aggregates and of the filler in an asphalt mixture. Besides, your mineralogical composition presented the same present minerals in the composition of conventional aggregates used in paving. The results evaluation of the volumetric composition of the mixtures containing residue indicates that it can use up to 30% of residue in substitution to the conventional aggregates. The evaluation of the mechanical behavior of those mixtures indicates that the residue increment in the studied mixtures caused an increase of the stability and a reduction of the resistance to the traction. The values obtained in the resistance to the traction meet below the minimum value specified by DNIT, but close to the value obtained in the conventional mixture. When taking in consideration the susceptibility of the same ones to the humidity, the results indicate that she can use up to 25% of residue